A general strategy to synthesize high-level N-doped porous carbons via Schiff-base chemistry for supercapacitors. Issue 26 (13th June 2018) - Zhu, Dazhang; Jiang, Juxiang; Sun, Dongmei; Qian, Xiaoyu; Wang, Yawei; Li, Liangchun; Wang, Zhiwei; Chai, Xiaolan; Gan, Lihua; Liu, Mingxian
Abstract : A general Schiff-base strategy was developed to efficiently synthesize high-level N-doped porous carbons with tunable geometry and pore structure for supercapacitors. Abstract : Recently, the synthesis of porous carbon-based materials, especially those with unique geometry, narrow pore size distribution, large surface area and high nitrogen content, has been highly attractive for widespread applications, but remains a great challenge. Herein, we demonstrate a novel strategy for highly efficient synthesis of high-level N-doped microporous carbon spheres (N-MCSs) based on a very simple Schiff-base reaction of 3, 3′-diaminobenzidine and p -phthalaldehyde in ethanol solvent without any catalyst or tedious procedure, followed by a common one-step carbonization–activation process. The N-MCSs exhibit a spherical morphology, regular micropores, high surface areas and high nitrogen contents (up to 8.71 at%). N-MCSs used as supercapacitor electrodes deliver high gravimetric capacitance, good rate capability and cycling stability. More importantly, the synthetic approach can be extended to other Schiff-base systems such as p -phthalaldehyde and p -phenylenediamine or ethylenediamine to fabricate porous carbon-based materials with high nitrogen species, tunable morphology and pore structure. The general strategy presented in this study opens up a new window for heteroatom doping, geometry and structure control, and highlights the great potential of well-developed carbon-based materials for extensive applications.